Winnie the Pooh: Tigger is Unbounced - Milne, Alan Alexander (Egmont Children's Books Ltd, 1999)
Even a Tigger can get too bouncy for one's own good. When Pooh & his pals try to unbounce him, their well-thought-out plan backfires.
Keywords: Juvenile Fiction; Toys, Dolls, Puppets